Macrophage Derived Platelet Activating Factor Implicated in the Resolution Phase of Gouty Inflammation. (24th September 2014) - Yagnik, Darshna
Abstract : Human blood derived in vitro differentiated monocytes or macrophages are a population of cells which have been investigated over the years to determine the role these cells play in the resolution phase of gout. Macrophages are able to phagocytose monosodium urate monohydrate (MSU) crystals without releasing inflammatory factors. This study analysed macrophage platelet activating factor secretion and its possible role in the pathway of gout resolution. Analysis of sunatants from in vitro differentiated macrophages stimulated with MSU crystals revealed the secretion of platelet activating factor (PAF) 1.54 ± 0.10 mean ± SEM; ng/mL per 10 6 cells. This secretion was absent in immature monocytes treated similarly. When these monocytes were pretreated with recombinant human PAF-acetylhydrolase (rhuPAF-AH) and MSU crystals resulted in TNF α suppression. Addition of WEB2086, a platelet activating factor (PAF) antagonist, to differentiated macrophages with MSU crystals unmasked TNF α secretion0.7 ± 0.06 mean ± SEM; ng/mL per 10 6 cells. This study identifies a role for PAF and the PAF receptor antagonist in the pathway by which macrophages ingest MSU crystals and resolve the concomitant inflammation.